Chemokine receptor CCR5 and CXCR4 might influence virus replication during IBDV infection. (June 2017) - Ou, Changbo; Wang, Qiuxia; Yu, Yan; Zhang, Yanhong; Ma, Jinyou; Kong, Xianghui; Liu, Xingyou
Abstract: Both CCR5 and CXCR4 are important chemokine receptors and take vital role in migration, development and distribution of T cells, however, whether they will influence the process of T cell infiltration into bursa of Fabricius during infectious bursal disease virus (IBDV) infection is unclear. In the current study, CCR5 and CXCR4 antagonists, Maraviroc and AMD3100, were administrated into chickens inoculated with IBDV, and the gene levels of IBDV VP2, CCR5, CXCR4 and related cytokines were determined by real-time PCR. The results showed that large number of T cells began to migrate into the bursae on Day 3 post infection with IBDV and the mRNA of chemokine receptors CCR5 and CXCR4 began to increase on Day 1. Moreover, antagonist treatments have increased the VP2, CCR5 and CXCR4 gene transcriptions and influenced on the gene levels of IL-2, IL-6, IL-8, IFN-γ, TGF- β 4, MHC-I and MDA5. In conclusion, the chemokine receptors CCR5 and CXCR4 might influence virus replication during IBDV infection and further study would focus on the interaction between chemokine receptors and their ligands. Highlights: The mRNA of chemokine receptors CCR5 and CXCR4 began to increase on Day 1 post IBDV infection. CCR5 and CXCR4 antagonist treatments increased the VP2 gene transcriptions. The chemokine receptors CCR5 and CXCR4 might play vital role in T cell migration.